(64)Cu-labeled melanin nanoparticles for PET/CT and radionuclide therapy of tumor - Zhou, Huijun (Nanomedicine, 2020)
Melanin is a group of natural pigments found in living organism. It can be used for positron emission tomography (PET) imaging due to its inherent chelating ability to radioactive cupric ion. This study was to prepare (64)Cu-labeled PEGylated melanin nanoparticles ((64)Cu-PEG-MNPs), and to further take advantage of the enhanced permeability and retention (EPR) effect of radiolabeled nanoparticles to realize the integration of tumor diagnosis and treatment. We successfully synthesized PEG-MNPs. Saline and serum stability experiments demonstrated good stability. PET/CT showed high tumor aggregation. Moreover, (64)Cu-PEG-MNPs resulted in a therapeutic effect on the A431 tumor-bearing mice in the treatment group. The pathological results further confirmed that the therapeutic doses of (64)Cu-PEG-MNPs cause pathological changes of tumor tissues while showing minimal toxicity to normal tissues. Our data successfully demonstrate the good imaging performance of (64)Cu-PEG-MNPs on A431 tumors and further proved its therapeutic effect, highlighting a great potential in targeted radionuclide therapy.